Body-weight dependent dose coefficients for adults exposed to idealised external photon fields. (30th October 2018) - Chang, Lienard A; Borrego, David; Lee, Choonsik
Abstract: In epidemiological investigations of cancer risk from occupational exposure, it is important to obtain an organ-specific dose for each cohort member for accurate risk analysis. To date, dose conversion coefficients, which convert physical dose measurement to organ dose, are only available for individuals with reference body size, which can differentially bias the estimated organ dose depending on the body mass index of cohort members. In the current study, we calculated the organ dose coefficients applicable to adult males and females with various body weights by using the Monte Carlo radiation transport technique combined with a library of body size-dependent hybrid computational phantoms exposed in six idealised irradiation geometries. We adapted the eight adult male phantoms, 175 cm tall with weights of 60, 70, 80, 90, 100, 110, 120 and 130 kg, and the nine adult female phantoms, 165 cm tall with weights of 50, 60, 70, 80, 90, 100, 110, 120 and 130 kg. The radiation transport was simulated using MCNPX 2.7 Monte Carlo code. Phantoms were irradiated by external photon fields in anterior posterior (AP), posterior-anterior, right and left lateral, rotational, and isotropic geometries. The results showed that the 60 kg adult male phantom shows 1.33-, 1.43-, 1.44- and 1.52-fold greater dose coefficients for the lungs, heart, stomach, and liver, respectively, than the 120 kg adult male phantom at 0.1 MeV in AP geometry. We derived exponential correlation between organ dose coefficients and body weight to facilitate calculation of organ dose coefficients for a given weight. The comprehensive organ dose coefficients and exponential regression model can be used to estimate more accurate organ dose for individuals of the two genders with various body weights exposed to external photon radiation.